Abnormalities and Possible Mosaicism During Embryonic Cell Division After Cold Shock in Zygotes of the Pacific White Shrimp, Litopenaeus vannamei, Related to Failure of Induction of Tetraploidy and Triploidy. Issue 3 (1st May 2014) - Zúñiga-Panduro, Manuel de Jesús; Casillas-Hernández, Ramón; Garza-Torres, Rodolfo; Guerrero-Tortolero, Danitzia A.; Grijalva-Chon, José Manuel; Campos-Ramos, Rafael
Abstract: Abnormalities and possible mosaicism during embryonic cell division after cold shock of zygotes of Litopenaeus vannamei (Boone, 1931 ) were related to the failure of induction of polyploidy. Eggs were treated to 10 minutes cold shock at 8^° C to arrest the second polar body (triploid-induced eggs) or first cleavage (tetraploid-induced eggs). In both cases, asynchrony and abnormalities among embryos were observed. In some triploid-induced eggs, three haploid pronuclei, instead of two, were seen at the center of the egg, and none in the periphery. These three nuclei may serve to evaluate methods of triploid induction in penaeids. In tetraploid-induced eggs, a tetrapolar or a bipolar spindle was inferred. The common abnormality in the anaphase with a tetrapolar spindle came with an off-center position of the nucleus, ending in a 2-cell stage with either a blastomere with one complete nucleus (4n) or two separate nuclei (2n and 2n ), both with one anucleated (0n) blastomere. Other abnormalities produced 3- and 4-cell stages with one to three anucleated (0n) blastomeres, including one putative mosaic. In triploid-induced eggs, the main abnormalities came with syngami between two pronuclei only, ending in a putative 4-cell stage 1:1 triploid (3n) : diploid (2n) mosaic egg or without syngamy, ending in a putative 4-cell stage 2:1:0 diploid 2(2n) : haploid (n) : anucleated (0n) mosaic egg, and perhaps a putative 1:1 diploid (2n) : haploid (n) mosaic egg. Less frequent 4-cell stage arrangements had 1:1 sextaploid (6n) : anucleated (0n) and 1:3 one nucleated (3n) and three anucleated (0n) blastomeres. We suggest that inherent problems in L. vannamei embryos are related to lethal occurrences of putative nauplii mosaics. Alternative methods to induce polyploidy are needed for this species.